2023
DOI: 10.3390/laws12030056
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of the Rights and Obligations of the Manager of a Limited Liability Company: Managerial Legislative Basis

Abstract: The rights and obligations of an executive as a top manager of a limited liability company seem to be a long-settled question. However, the opposite is true. We were particularly interested in the question of the rights and obligations of the manager as a statutory body of the most widespread type of business company. A very important issue is the definition of the relationship between the limited liability company and the manager. The reason for this is the fact that it is a business–legal relationship and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…When Tp = 5, the lead hospital tends to choose to build inefficiently, while the primary healthcare institutions choose to actively participate in the construction of the health community. With a gradual increase in the information and management authority ceded by the primary healthcare institutions, the lead hospital can use its influence on its members to build an organizational structure with strong relationships, thus enhancing the mobilization and linkage capacity of the alliance [43]. From Figure 2b, it can be observed that an increase in Tp somewhat prevented the primary healthcare institutions from participating in the construction of the CMC, which reflects their hidden concern about the loss of core resources and independence.…”
Section: The Information and Management Authority Ceded By The Primar...mentioning
confidence: 99%
“…When Tp = 5, the lead hospital tends to choose to build inefficiently, while the primary healthcare institutions choose to actively participate in the construction of the health community. With a gradual increase in the information and management authority ceded by the primary healthcare institutions, the lead hospital can use its influence on its members to build an organizational structure with strong relationships, thus enhancing the mobilization and linkage capacity of the alliance [43]. From Figure 2b, it can be observed that an increase in Tp somewhat prevented the primary healthcare institutions from participating in the construction of the CMC, which reflects their hidden concern about the loss of core resources and independence.…”
Section: The Information and Management Authority Ceded By The Primar...mentioning
confidence: 99%
“…Some scholars have emphasized the importance of legislative foundations in defining the rights and obligations of limited liability company managers. In addition, they have assessed their own knowledge and skills [15]. This legal framework provides clear regulations and boundaries for managers' actions, ensuring they comply with legal requirements in fulfilling their duties and exercising their power.…”
Section: Managerial Myopia Behavior and Enterprise Sustainability Per...mentioning
confidence: 99%
“…The key findings by scientists Peráček and Kaššaj (2023) show that the manager in a limited liability company has one of the most important functions and they have a wide range of rights and responsibilities. Such a wide range of rights and duties also requires a high level of responsibility.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%